Socio-technical networks modulate on-farm technological innovations in wool production of North Patagonia, Argentina - Gonzalez, Ezequiel Bernardo; Easdale, Marcos Horacio; Sacchero, Diego Mariano (Elsevier, 2021)
Socio-technical networks in the agricultural sector are complex and are key in technological innovation processes. Some relevant on-farm management decisions depend on a negotiation process involving different factors, some of which include the interplay between farmers and off-farm services. We assessed the role of the relationships between farms and shearing contractors, with respect to the influence in the adoption of pre-lambing wool shearing at farm-level in Northern Patagonia, Argentina. In particular, we analysed quantitative data on the amount and quality of pre- and post-lambing shearing of wool and the working activity of shearing services by focusing on the date of shearing as a key decision, which interconnects them. The first two months of the shearing season were associated with pre-lambing shearing, for which the simultaneous activity of the shearing contractors was higher. The last two months of the shearing season were associated with post-lambing shearing, which reached a fourth portion of total wool shorn as well as lower wool quality. Results are discussed with respect to the factors constraining changes in such periods and in functional features of the socio-technical networks, which have consequences on pre-lambing shearing adoption. A combination of environmental, productive, and social factors may be limiting further adoption of pre-lambing shearing. The socio-technical networks approach offers new insights for a more comprehensive understanding of on-farm technological adoption. We emphasize the role of socio-technical networks in modulating technological innovation processes at a farm level.